Clean7 : supercharge your body's natural ability to heal itself : a one-week breakthrough detox program - Junger, Alejandro (HarperOne, 2019)
"In this long-awaited follow-up to the definitive detox program, New York Times bestselling author Dr. Alejandro Junger delivers a detailed, personalized, and medically proven 7-day program to rid our bodies of the multitude of toxins that keep us from living well and feeling our best"--